2005
DOI: 10.1029/2004jb003462
|View full text |Cite
|
Sign up to set email alerts
|

Melt distribution in olivine rocks based on electrical conductivity measurements

Abstract: [1] Properties of partially molten rocks depend strongly on the grain-scale melt distribution. Experimental samples show a variety of microstructures, such as melt lenses, layers, and multigrain melt pools, which are not readily explained using the theory for melt distribution based on isotropic interface energies. These microstructures affect the melt distribution and the porosity-permeability relation. It is still unclear how the melt distribution changes with increasing melt fraction. In this study, electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 31 publications
5
105
0
Order By: Relevance
“…Competing observations have been reported about the degree of partial melt required for efficient interconnectivity (and thus a detectable reduction in electrical resistivity), from values as low as 0.02% (Drury and Fitz Gerald, 1996) to values of 2-3% (Faul, 1997;ten Grotenhuis et al, 2005). Drury and Fitz Gerald (1996) observed that very thin (1.0-1.5 nm) films can be found on grain boundaries that can only be observed using high-resolution electron microscopy and are not observable by light or SEM observations.…”
Section: Discussionmentioning
confidence: 99%
“…Competing observations have been reported about the degree of partial melt required for efficient interconnectivity (and thus a detectable reduction in electrical resistivity), from values as low as 0.02% (Drury and Fitz Gerald, 1996) to values of 2-3% (Faul, 1997;ten Grotenhuis et al, 2005). Drury and Fitz Gerald (1996) observed that very thin (1.0-1.5 nm) films can be found on grain boundaries that can only be observed using high-resolution electron microscopy and are not observable by light or SEM observations.…”
Section: Discussionmentioning
confidence: 99%
“…Cementation factor for melt is best represented by m = 1.3 (ten Grotenhuis et al 2005). Electrical conductivity of molten rock was estimated to range between 1 and 30 S m −1 (Lebedev & Khitarov 1964;Tyburczy & Waff 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a geotherm can be constructed based on these laboratory results which demonstrate a conductivity dependence on temperature and whether the mantle may be layered (Xu et al 1998). These data provide a background level from which additional parameters can be investigated such as the effect of partial melts on the conductivity in olivine (for melts from 0.01 to 0.1% there is an increase in conductivity by at least two orders of magnitude; ten Grotenhuis et al 2005).…”
Section: Geophysical Implicationsmentioning
confidence: 99%